The region-of-origin effect on the preferences of financial institution's customers: Analysis of the influence of ethnocentrism - José Manuel García-Gallego; Antonio Chamorro Mera (BRQ Business Research Quarterly, 2016)
Summary The financial crisis that started in the USA in 2007 has obliged many small financial entities in southern Europe to undertake mergers in order to comply with the stability and solvency policies established by the European Central Bank. In Spain, this situation has led to a profound restructuring of the financial system, obliging many of these institutions to decide whether or not to maintain their regional brand identity after such a merger. The purpose of this study was twofold: on the one hand, to analyze the importance customers attach to the origin of their usual financial institution and the relative utility they give to the three levels of brand origin presented: regional, national and foreign, and, on the other, to assess whether consumers' level of ethnocentrism modifies their preference structure and, if so, to identify the profile of the individuals composing each segment. The technique of Conjoint Analysis was applied to a survey of 427 customers. The results showed the bank's to be the attribute with the greater importance in forming customers' preferences than other characteristics of the institution such as the treatment by employees, the location of offices, the electronic banking services, and the number of social activities the entity carries out in the region. In addition, the respondents prefer regional brand origin over national and foreign. Both the importance and the utility attached to the regional brand origin increase with higher levels of consumer ethnocentrism. The findings of this study will serve to these entities as a guide for their decision-making regarding brand management."
Keywords: 650; Ethnocentrism; Region of origin; Financial sector; Preferences; Conjoint analysis